Zur Einführung: Sprachliche und multimodale Konstruktionen von Räumlichkeit und Zeitlichkeit im Diskurs - Held, Gudrun; Messner, Monika (Linguistik Online, 2026)
This special issue investigates the linguistic and multimodal representation of spatiality and temporality as core cognitive dimensions in contemporary discourse. Emphasizing their interdependence, the contributions examine how space and time are conceptually integrated, semantically mediated, and pragmatically realized across a range of communicative and medial contexts. Drawing on approaches from cognitive linguistics, interactional linguistics, and multimodality research, the 11 papers offer empirical insights into the dynamic interplay of verbal, visual, and embodied resources. In doing so, the volume highlights how spatial and temporal meanings are discursively constructed, negotiated, and contextually anchored in diverse forms of communicative practices.